Current and future landscape of targeted therapy in HER2-positive advanced breast cancer: redrawing the lines. (January 2022) - Simmons, Christine; Rayson, Daniel; Joy, Anil Abraham; Henning, Jan-Willem; Lemieux, Julie; McArthur, Heather; Card, Paul B.; Dent, Rebecca; Brezden-Masley, Christine
Background: Evidence to date supports continued human epidermal growth factor receptor 2 (HER2) suppression beyond progression on HER2-directed therapy for advanced HER2-positive breast cancer. Data from several phase II and III trials evaluating HER2-directed therapy following second-line T-DM1 have recently become available. Methods: We performed a systematic search of the published and presented literature to identify phase II and phase III trials assessing novel HER2-targeted agents as third-line therapy or beyond for HER2-positive advanced breast cancer using search terms 'breast cancer' AND 'HER2' AND 'advanced' AND ('phase II' OR 'phase III'). Results: Eight clinical trials reporting efficacy outcomes on third-line or greater HER2-directed therapy for HER2-positive advanced breast cancer were identified. In phase III trials, margetuximab and neratinib combinations demonstrated significant 1.3-month (hazard ratio, HR = 0.71, p  < 0.001) and 0.1-month (HR = 0.76, p  = 0.006) net improvements in median progression-free survival (PFS), respectively, with no significant improvements in overall survival (OS). Tucatinib added to trastuzumab and capecitabine demonstrated a significant 2.7-month improvement in median PFS (HR = 0.57, p  < 0.00001) and a 5.5-month improvement in median OS (HR = 0.73, p  = 0.004) in a randomized phase II trial, including significant clinical benefit for patients with brain metastases. Finally, trastuzumab-deruxtecan, zenocutuzumab, and poziotinib demonstrated benefit in phase II trials with the most robust overall response rate (62.0%) and median duration of response (18.2 months) observed for trastuzumab-deruxtecan among heavily pretreated patients. Conclusion: Tucatinib plus trastuzumab and capecitabine significantly prolongs OS, and promising preliminary response outcomes for trastuzumab-deruxtecan suggest that sequencing of these regimens following second-line therapy is reasonable.